2021
DOI: 10.1016/j.marenvres.2020.105232
|View full text |Cite
|
Sign up to set email alerts
|

Seabird diet analysis suggests sudden shift in the pelagic communities of the subtropical Northeast Atlantic

Abstract: The dynamics of the subtropical pelagic ecosystems of the Northeast Atlantic are still poorly known due to the high costs associated with sampling large oceanic areas. Top predators can be used as alternative low-cost samplers and indicators of the temporal variability of such systems. To study the variation in the composition of pelagic species through time in the broad Canary current region, we analysed foraging trips and regurgitations of Cory's shearwaters Calonectris borealis nesting on Selvagens islands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…White-faced Storm Petrel does not seem to be associated with seamounts or core upwelling areas in the African coast, in contrast with other Procellariiform species from this and adjacent colonies. For example, Cory's shearwater Calonectris borealis from Selvagem Grande forage the oceanic domain around the islands, the African continental shelf (from Morocco to Mauritania), and the nearest seamounts (e.g., Alonso et al 2012;Ramos et al 2013;Romero et al 2021). On the other hand, the Bulwer's petrel explores areas around the colony and waters close to the Azorean archipelago (mid-Atlantic) (Dias et al 2016), but birds from the Canary Islands also use the shelf-break to forage during the breeding season (Rodríguez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White-faced Storm Petrel does not seem to be associated with seamounts or core upwelling areas in the African coast, in contrast with other Procellariiform species from this and adjacent colonies. For example, Cory's shearwater Calonectris borealis from Selvagem Grande forage the oceanic domain around the islands, the African continental shelf (from Morocco to Mauritania), and the nearest seamounts (e.g., Alonso et al 2012;Ramos et al 2013;Romero et al 2021). On the other hand, the Bulwer's petrel explores areas around the colony and waters close to the Azorean archipelago (mid-Atlantic) (Dias et al 2016), but birds from the Canary Islands also use the shelf-break to forage during the breeding season (Rodríguez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The at-sea distributions of most seabirds are linked to spatial distribution of prey, their abundance, and availability (Hunt and Schneider 1987;Fauchald et al 2000;Depot et al 2020). The diet of seabirds can reflect changes that occur at lower trophic levels, and thus, seabirds can be used as indicators helping to monitor the marine environment (Romero et al 2021). Information on at-sea behavior and space-use of pelagic seabirds is essential to understand their role in ocean ecosystems and is also increasingly used to inform marine spatial planning (Camphuysen et al 2012;Oppel et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Seabird colonies located within the same marine region but surrounded by contrasting oceanographic/hydrographic features may experience heterogeneous environmental conditions influencing prey distribution and composition (Alonso et al, 2018;Kitaysky and Golubova, 2000;Montevecchi and Myers, 1995). This may lead to substantial differences in the use of trophic resources among populations (Angel et al, 2016;Tremblay and Cherel, 2003) but since diet studies often target a single colony site/population (Hamer et al, 2007;Romero et al, 2021) such variability is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the trophic and movement plasticity of Calonectris shearwaters (Alonso et al, 2018;Romero et al, 2021) and the marked variation in environmental conditions between the three Mediterranean regions investigated (Bonanno et al, 2014a;Millot and Taupier-Letage, 2005;Vetrano et al, 2010) as well as the spatial constrains imposed by central-place foraging during reproduction, we expect differences in the trophic niche and high spatial segregation among populations during breeding period. Conversely, because spatial constraints due to central-place foraging vanish during non-breeding and because previous studies on other Scopoli's shearwater populations have shown that they all exploit three main coastal regions off West Africa (González-Solís et al, 2007;Grémillet et al, 2014;Müller et al, 2014), we do not expect a marked inter-colony spatial segregation of exploited oceanic areas.…”
Section: Introductionmentioning
confidence: 99%